Content of metals and metabolites in honey originated from the vicinity of industrial town Košice (eastern Slovakia) - Kováčik, Jozef; Grúz, Jiří; Biba, Ondřej; Hedbavny, Josef (Environmental science and pollution research international, 2016)
Composition of three types of honey (mixed forest honey and monofloral-black locust and rapeseed honeys) originated from the vicinity of an industrial town (Košice, Slovak Republic) was compared. Higher content of minerals including toxic metals in forest honey (1358.6 ng Ni/g, 85.6 ng Pb/g, and 52.4 ng Cd/g) than in rapeseed and black locust honeys confirmed that botanical origin rather than the distance for eventual source of pollution (steel factory) affects metal deposition. Benzoic acid derivatives were typically more accumulated in forest but cinnamic acid derivatives and some flavonoids in rapeseed honey (in free and/or glycoside-bound fraction). In terms of quantity, p-hydroxybenzoic and p-coumaric acids were mainly abundant. Total phenols, thiols, and proteins were abundant in forest honey. Some metals and phenols contributed to separation of honeys based on principal component analysis (PCA). Native amount of 5-(hydroxymethyl)furfural was not related to honey type (~11 μg/g) and was elevated after strong acid hydrolysis (200-350 μg/g) but it did not interfere with the assay of phenols by Folin-Ciocalteu reagent. This is the first report of metals and metabolites in the same study, and data are discussed with available literature. We conclude that black locust (acacia) honey is the most suitable for daily use and that central European monofloral honeys contain lower amounts of toxic metals in comparison with other geographical regions.
Keywords: flavonoidy; Antioxidants; med; Furaldehyde; Flavonoids; fenoly; Phenols; Metals; Food safety; Heavy metals; Slovakia; Mass spectrometry; Industry; Acacia; Honey; kovy; Minerals; 2-furaldehyd; průmysl; akácie; minerály; Slovenská republika; Robinia